KOMUNITAS SISTEM SEL SEBAGAI WADAH PEMBINAAN IMAN PASANGAN KELUARGA MUDA - Adinuhgra, Silvester (STP St. Bonaventura Medan, 2020)
This article departs from the author's own experience as a young family who was still a toddler. As a new family, the author is aware that there are so many obstacles to face. The crises faced at the beginning of marriage are certainly faced by almost all young married couples. In this kind of reality, families need assistance, and of course the greatest hope is in the Church. But unfortunately, the Church has not demonstrated or displayed a pastoral pattern of assisting or coaching young families. So, as an offer, the mentoring pattern in the cell system community is a preventive step for young family couples to find a living climate of faith that leads them to the communion of life and love